北海道北部の風力発電機周辺で見つかった鳥類死体の剖検所見 - 吉野, 智生; 21611; 浅川, 満彦; 1839; ASAKAWA, Mitsuhiko; 9416 (利尻町立博物館, 2021)
Article Postmortem examinations of avian carcasses including Haliaeetus albicilla, Milvus migrans and Larus schistisagus found at bases of the wind power generators of Tomamae-cho and Ishikari-city in northern Hokkaido, Japan, were performed, and each pathological finding were given. journal article